Protection of human γB-crystallin from UV-induced damage by epigallocatechin gallate: spectroscopic and docking studies. Issue 9 (13th July 2016) - Chaudhury, Susmitnarayan; Bag, Sudipta; Bose, Madhuparna; Das, Amit Kumar; Ghosh, Ananta Kumar; Dasgupta, Swagata
Abstract : The transparency of the human eye lens depends on the solubility and stability of the structural proteins of the eye lens, the crystallins. Abstract : The transparency of the human eye lens depends on the solubility and stability of the structural proteins of the eye lens, the crystallins. Although the mechanism of cataract formation is still unclear, it is believed to involve protein misfolding and/or aggregation of proteins due to the influence of several external factors such as ultraviolet (UV) radiation, low pH, temperature and exposure to chemical agents. In this article, we report the study of UV induced photo-damage (under oxidative stress) of recombinant human γB-crystallin in vitro in the presence of the major green tea polyphenol, (−)-epigallocatechin gallate (EGCG). We have shown that EGCG has the ability to protect human γB-crystallin from oxidative stress-induced photo-damage.